The Impact and Response of Android Mobile Application Utilization of Health Consultations by Pregnant Women in Indonesia - Nurdiana , Astri; Andriani , Eka; ., Carudin (International Journal of Membrane Science and Technology, 2023)
The targets pertaining to Sustainable Development Goals for the period spanning from 2020 to 2021 have been revised downwards, notwithstanding a notable surge of 25 percent in the use of mobile-based health applications. Hence, the objective of this study is to create a mobile application called "Nutribid" that provides online counselling services for reproductive health and nutrition, specifically designed for Android devices. The participants of this research were 56 pregnant women residing in Purwadana Village, Indonesia, who utilised mobile devices equipped with the Android operating system. The findings indicate that a significant majority of the participants, above 90%, expressed agreement with the ease of identification, download, and use of the Nutribid application. Nevertheless, it is worth noting that a significant proportion, specifically 60.7% of the participants, expressed their dissatisfaction with the colour scheme employed in the application. Conversely, an overwhelming majority of the respondents concurred that the Nutribid application menu possesses commendable attributes such as ease of recognition, discoverability, legibility, and usability. The utilisation of mobile health applications has witnessed significant growth, yet, its integration into Indonesian society encounters many challenges attributed to the limited internet network infrastructure.